MENINGKATKAN PEMAHAMAN SISWA DALAM MEMASUKI PERSIAPAN BERUMAH TANGGA MELALUI LAYANAN INFORMASI KLASIKAL KELAS XII IPS - Apriani, Uci; Asrori, Asrori; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe method used is descriptive method with research form research counseling guidance action, and is collaborative. The research location is located at State Senior High School 10 Pontianak, especially in class XII IPS 2, amounting to 34 students. Tekinik data collection used direct observation techniques, measurement techniques and communication techniques with data collection tool that is the observation sheet and test questions. Data analysis technique used is calculate the result of value obtained and percentage.From the data obtained shows that by using the activities of classical information services can improve students' understanding on the preparation to enter married life in class XII IPS 2 State Senior High School 10 Pontianak.Keyword : collaborative, classical, preparation to enter married